Improving Marketing Research In Food Enterprises - Baymukhamedova Gulnoza Fattakhovna (Academia One Publishing, 2024)
Nowadays, the demand for children's food and drinks is increasing. Although the overall nutritional profile of some products marketed for children has improved, some gaps and gaps remain in the market for children's food products. In closing this gap, it is essential to clearly define the importance of advertising and marketing to children. This article discusses the role of marketing in the domestic market for baby food products and the marketing strategies used to appeal to children and adolescents.
Keywords: marketing; advertising; branding